Chiral lanthanide-directed self-assembly : ligand substitution as a path to functionally diverse supramolecular complexes - Caffrey, David F. (Trinity College (Dublin, Ireland). School of Chemistry, 2014)
Entitled “Chiral Lanthanide-Directed Self-Assembly: Ligand Substitution as a Path to Functionally Diverse Supramolecular Complexes”, this thesis is divided into seven chapters. Chapter 1, the introduction, aims to address topics pertinent to the research described in the following chapters. This chapter begins with an overview of the lanthanide metal ions, detailing the advantages offered by their unique photophysical and magnetic properties. An account of the various strategies employed for their inclusion into supramolecular complex designs is then given, focusing primarily on the macrocyclic and self-assembly approaches. Upon review of some recent lanthanide macrocyclic systems, the remainder of the chapter serves to introduce lanthanide-directed self-assembly. A comprehensive literature review of relevant examples of monometallic, multimetallic, and chiral lanthanide self-assemblies is first provided, before later describing related systems developed previously within the Gunnlaugsson group, the designs of which inspired this PhD project.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin